Calretinin expression in molecular subtypes of invasive carcinoma breast - Venugopal, Suryagayathri; J., Cicy P.; S., Deepa; Sundaram, Sankar (International Journal of Research in Medical Sciences, 2020)
Background: Breast cancer is a leading cause of cancer death in women worldwide. Breast carcinoma is currently managed by assessing clinicopathological features. Elucidation of molecular mechanisms of pathogenesis of breast carcinoma may lead to the development of new targeted therapies, particularly in triple negative cancers. Literature shows a few studies on the expression of calretinin in breast carcinoma particularly in basal like type and its prognostic significance. In this study, authors are trying to assess the expression of a new marker calretinin in different molecular subtypes of invasive carcinoma breast. Methods: This study was done in 107 cases of invasive carcinoma breast specimens received in Department of Pathology, Government Medical college, Kottayam from December 2017 to May 2019. Results: Among the molecular subtypes, Basal like tumours showed 68.4% of cases with high level and 31.6% of cases with low level calretinin expression which is comparable with the study by Farrag et al. All the other molecular subgroups showed predominantly low level of calretinin expression. Conclusions: Different molecular subtypes of invasive carcinoma breast showed varied calretinin expression. High level calretinin expression was significantly associated with grade 3 (p value = 0.002), ER negativity (p = 0.004), PR negativity (p = 0.018) and Basal like molecular subtype (p : <0.001). This suggests that calretinin might play a role in pathogenesis of basal like breast carcinomas.